Bistorta tenuifolia var. gidarensis (Polygonaceae), a new variety from India - Rai, Ishwari Datt; Singh, Gajendra; Rawat, Gopal Singh (Phytotaxa, 2013)
During a botanical excursion of the alpine meadows in the state of Uttarakhand, we came across a viviparous species under the genus Bistorta (Polygonaceae). Subsequently, the taxon was also recorded from the Great Himalayan National Park, Himachal Pradesh. The gross morphology suggested this plant belong to B. tenuifolia but we found differences in the shape of perianth lobe and the size of stamens from those of the typical B. tenuifolia. On the basis of the acute perianth lobes, the minute stamens that are included in the perianth and the reniform anthers, we describe a new variety, B. tenuifolia var. gidarensis and compared it with the nominal variety and the related species B. vivipara.